Nutritional value and therapeutic potential of Moringa oleifera: a short overview of current research - Nabila, Bibi; Nadia, Rahman; Muhammad, Qasim Ali; Noormazlinah, Ahmad; Farzana Sarwar, Sarwar (Taylor Francis Online, 2023)
A member of the Moringaceae family, Moringa Oleifera Lam is a perennial deciduous tropical tree known as the ‘Miracle Tree’ for its medicinal and nutritional benefits. Food and nutrition are crucial aspects of the development and maintenance of healthy health. Moringa oleifera is a multi-purpose herbal bush that is used as both human food and a medical alternative all over the world. Various parts of the tree are used to treat chronic diseases such as hypertension, heart disease, inflammation, oxidative stress, diabetes, and cancer. Moringa is an excellent source of essential nutrients and has been found to have a significant impact on improving nutritional deficiencies in populations with limited access to food. Moringa oleifera contains essential amino acids, carotenoids, minerals, fats, carbohydrates, proteins, phytochemicals, vitamins, and fibre. Moringa offers nutritional and economic advantages, medicinal and therapeutic uses, and future biological potential for human well-being.